2020
DOI: 10.1007/s40430-020-02399-y
|View full text |Cite
|
Sign up to set email alerts
|

Energy, exergy, and exergoeconomic evaluations of a micro-trigeneration system

Abstract: This study presents energy, exergy, and exergoeconomic assessments for a natural gas-fueled micro-trigeneration unit, which encompasses an internal combustion engine (ICE), an absorption refrigeration system (ammonia-water), and a heat recovery unit. The energy system is designed to meet the electricity and cooling demands of a university building, while heat is directed to a biodiesel plant located on site. The analyses comprehended energy and exergy parameters (first and second laws of thermodynamics). Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The same conclusions were obtained by Shokati et al [81,82]. As mentioned by Reference [33], such a level of knowledge on the cost-benefit assessment of improvements is provided by exergoeconomics only.…”
Section: D )supporting
confidence: 74%
See 2 more Smart Citations
“…The same conclusions were obtained by Shokati et al [81,82]. As mentioned by Reference [33], such a level of knowledge on the cost-benefit assessment of improvements is provided by exergoeconomics only.…”
Section: D )supporting
confidence: 74%
“…The values obtained for the ICE indicate that there are margins for improvement; however, this piece of equipment is commercially available and mass-produced, preventing interventions, and therefore, substituting the engine for another with higher efficiency has limited applicability. This approach was also followed by the authors of Reference [33], who identified that the absorber heat exchanger, steam generator, and heat recovery unit could benefit from improvements.…”
Section: D )mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned by Marques et al [50] , exergy-based assessments, along with their discussions, can stimulate the adoption of co- and trigeneration systems, which are more efficient. At the time of writing, the coronavirus (COVID-19) crisis is having a significant impact across the energy sector and is hindering low-carbon energy transitions.…”
Section: Resultsmentioning
confidence: 98%
“…In this regard, the energy access sector needs stimulus beyond the COVID-19 era. The combined energy generation systems were adjudged as veritable means to drive the energy access beyond the COVID-19 pandemic crisis, for efficient energy solutions aimed at enhancing economic competitiveness, providing more affordable energy services, and reducing environmental impact [5].…”
Section: Introductionmentioning
confidence: 99%